2018
DOI: 10.1371/journal.pone.0208042
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic analysis of heart failure hospitalization among patients with chronic kidney disease: The Heart and Soul Study

Abstract: BackgroundPatients with chronic kidney disease (CKD) are at increased risk for heart failure (HF). We aimed to investigate differences in proteins associated with HF hospitalizations among patients with and without CKD in the Heart and Soul Study.Methods and resultsWe measured 1068 unique plasma proteins from baseline samples of 974 participants in The Heart and Soul Study who were followed for HF hospitalization over a median of 7 years. We sequentially applied forest regression and Cox survival analyses to s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 48 publications
1
20
0
Order By: Relevance
“…SPON1 (F‐spondin), a molecule associated with adverse clinical outcome, regulates migration and proliferation of macrophages in response to CpG, a pattern typical for bacteria and recognized by toll‐like receptor 9 . In human studies, SPON1 was found to correlate negatively with left ventricular ejection fraction and GFR in HF patients, which is in accordance with our results . SPON1 is also an independent predictor of HF and is associated with systolic dysfunction and was identified as a candidate gene for hypertension based on an animal study .…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…SPON1 (F‐spondin), a molecule associated with adverse clinical outcome, regulates migration and proliferation of macrophages in response to CpG, a pattern typical for bacteria and recognized by toll‐like receptor 9 . In human studies, SPON1 was found to correlate negatively with left ventricular ejection fraction and GFR in HF patients, which is in accordance with our results . SPON1 is also an independent predictor of HF and is associated with systolic dysfunction and was identified as a candidate gene for hypertension based on an animal study .…”
Section: Discussionsupporting
confidence: 89%
“…TRAP, an iron‐containing enzyme, resistant to inhibition by tartrate and activated in acidic conditions, is highly expressed in macrophages and was attributed a role in antigen processing . With regard to cardiovascular disease, an association between TRAP and lower risk of HF hospitalization in patients with chronic kidney disease was observed previously, but it remained unclear what mechanism could lead to this beneficial effect. The authors suggested that this may be a result of its inhibiting effect on osteopontin, which plays an important role in the development of atherosclerosis, but also mediates the profibrotic effect of M2 macrophages mentioned above .…”
Section: Discussionmentioning
confidence: 99%
“…SPON-1 is a cell adhesion protein important for axons and a major factor for vascular smooth muscle cell activity, which might explain the importance in cardiac toxicity (www.uniprot.org). In recent studies on patients with [34] or without [26,35] pre-existing hearth failure, SPON-1 was associated with incident or deteriorating heart failure. Interestingly, in one of the studies, chronic kidney disease was significantly interacting with the association, something that would be of concern to investigate further in our cohort [35].…”
Section: Discussionmentioning
confidence: 97%
“…We additionally identified 4 circulating proteins that were associated with multiple traits (FIGURE 7B), including SPON1, NMB, and FKBP7, which were each associated with increased LVEF and decreased ventricular volumes, and B3GNT8 which was associated with decreased volumes (FIGURE 7A ). Circulating SPON1 and FKBP7 have both been previously linked to atrial fibrillation, a known HF risk factor 43 , and SPON1 has been identified as a potential biomarker for HF hospitalization 44 .…”
Section: Proteome-wide Mendelian Randomization Prioritizes Circulating Proteins Associated With Adverse Hf Phenotypesmentioning
confidence: 99%